“LIBERTY OF TRADE FROM THE THRALDOM OF THE AUTOCRATS”: PROVISION OF SCHOOL TEXTBOOKS IN ONTARIO, 1850‐1909 - Clark, Penney (Canadian Journal of Education/Revue canadienne de l’éducation, 2006)
This article examines provision of elementary school readers in Ontario from 1850 to 1909. It traces the conflicts that arose due to the dual role of textbooks as economic commodity and democratic instrument of curriculum. It illuminates the strategies that three dominant stakeholders used in textbook provision to position themselves to best advantage in these conflicts: the Education Department, retail booksellers, and textbook publishers.. Key words: textbook publishing, school books, booksellers, political and economic contexts, curriculum history Cet article porte sur la fourniture de manuels aux écoles primaires de l’Ontario de 1850 à 1909. L’auteure relate les conflits qui ont surgi en raison du double rôle des manuels, comme objet de commerce et comme outil démocratique utilisé dans les programmes scolaires. L’article met en lumière les stratégies qu’ont utilisées trois catégories d’acteurs clés afin de se positionner au mieux de leurs intérêts dans ces conflits : le ministère de l’Éducation, les libraires et les maisons d’édition de ces manuels. Mots clés : édition de manuels scolaires, manuels scolaires, libraires, contextes politique et économique, histoire des programmes scolaires.